2018
DOI: 10.1007/s40687-018-0133-5
|View full text |Cite
|
Sign up to set email alerts
|

Moonshine for all finite groups

Abstract: In recent literature, moonshine has been explored for some groups beyond the Monster, for example the sporadic O'Nan and Thompson groups. This collection of examples may suggest that moonshine is a rare phenomenon, but a fundamental and largely unexplored question is how general the correspondence is between modular forms and finite groups. For every finite group G, we give constructions of infinitely many graded infinite-dimensional C[G]-modules where the McKay-Thompson series for a conjugacy class [g] is a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 43 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…In 2017, Dehority, Gonzalez, Vafa, and Van Peski [6] examined the question of the extent to which dimensions of irreducible representations of finite groups and Fourier coefficients of modular functions are related. They proved (see Theorem 1.1 of [6]) that the seemingly rare phenomenon of moonshine holds for every single finite group if we relax certain requirements. Namely, for every finite group G there is an infinite-dimensional graded G-module…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, Dehority, Gonzalez, Vafa, and Van Peski [6] examined the question of the extent to which dimensions of irreducible representations of finite groups and Fourier coefficients of modular functions are related. They proved (see Theorem 1.1 of [6]) that the seemingly rare phenomenon of moonshine holds for every single finite group if we relax certain requirements. Namely, for every finite group G there is an infinite-dimensional graded G-module…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…Theorem 1.1 of [6] guarantees that there is a G-module V G = n V G (n), q-graded traces T (1, g; τ ) which are modular functions for all g ∈ G, and non-negative integer multiplicities m i (n) for the representation spaces of each ρ i in V G (n). Moreover, the results in Section 5 of [6] guarantee that V G can be chosen to be asymptotically regular. Therefore, it suffices to construct the McKay-Thompson series for V (r) G for r > 1.…”
Section: Proofs Of Theorems 11 and 13mentioning
confidence: 99%
“…This proves all of the cases with r = 0 above. For the remaining cases with r > 0, we follow the method given in [12]. Let J, T 1 , .…”
Section: Basic Factsmentioning
confidence: 99%
“…. , a n such that J + a 1 T 1 + · · · + a n T n ≡ 0 mod q r+1 , then we have shown that v q (|G|) ≤ r. As in [12], this computation was carried out using Sage [36] by computing the kernel of the matrix of coefficients of J, T 1 , . .…”
Section: Basic Factsmentioning
confidence: 99%
See 1 more Smart Citation